Representation of Imperfection in TikTok’s Trend Wabi-Sabi: A Thematic Analysis - Fiella Widya Rahma Aprillia; Silvy Adelia (Hasanuddin University, 2026)
Social media has become an influential platform in shaping beauty standards by often promoting idealized and unattainable representations of physical appearance. In response to this phenomenon, the wabi-sabi trend on TikTok has emerged as an alternative narrative that celebrates imperfection, incompleteness, and authenticity. This study aims to examine how imperfection is represented in the wabi-sabi trend on TikTok and to identify the themes through which users reinterpret characteristics commonly perceived as flaws. This research uses thematic analysis following Braun and Clarke’s (2006) framework. Data were collected from TikTok videos under the hashtag #wabisabi that utilized the original King of the Hill audio associated with the trend. From an initial dataset of 100 videos, 20 videos met the engagement criteria. The findings reveal five major themes: feature deviations from beauty ideals, body imperfections as beauty, biological uniqueness, interpersonal relationships, and nature’s imperfection. These themes demonstrate that users celebrate various forms of imperfection. The study concludes that the wabi-sabi trend functions as a space that challenges beauty standards by embracing authenticity, diversity, and appreciation of imperfection.